2015
DOI: 10.1098/rsta.2014.0377
|View full text |Cite
|
Sign up to set email alerts
|

Are meteotsunamis an underrated hazard?

Abstract: Meteotsunamis are generated by meteorological events, particularly moving pressure disturbances due to squalls, thunderstorms, frontal passages and atmospheric gravity waves. Relatively small initial sea-level perturbations, of the order of a few centimetres, can increase significantly through multi-resonant phenomena to create destructive events through the superposition of different factors. The global occurrence of meteotsunamis and the different resonance phenomena leading to amplification of meteotsunamis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
124
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(132 citation statements)
references
References 81 publications
(154 reference statements)
6
124
1
1
Order By: Relevance
“…According to Pattiaratchi & Wijeratne's [13] review, meteotsunamis are multi-resonant phenomena, but primarily occurring when the speed of the atmospheric disturbance is close to equal the local shallow water wave celerity, then due to topographic resonance. All possible resonances depend in the bathymetry and geology of the coastline, while their timing with respect to tidal elevation or mean sea level (including storm surge) dramatically changes their impact.…”
Section: Will Climate Change Affect Future Tsunami Impacts?mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Pattiaratchi & Wijeratne's [13] review, meteotsunamis are multi-resonant phenomena, but primarily occurring when the speed of the atmospheric disturbance is close to equal the local shallow water wave celerity, then due to topographic resonance. All possible resonances depend in the bathymetry and geology of the coastline, while their timing with respect to tidal elevation or mean sea level (including storm surge) dramatically changes their impact.…”
Section: Will Climate Change Affect Future Tsunami Impacts?mentioning
confidence: 99%
“…While of course a single data point is not sufficient to draw general conclusions, it is noteworthy that the highest water level in 115 years from a meteotsunami was recorded in Fremantle, Western Australia. Pattiaratchi & Wijeratne [13] analysed weather and wave data from 25 events in 2014 and found that most occurred in winter, as cold fronts move onshore. The speculation is that, while the numbers may decrease as high-pressure belts expand during global warming, the resulting extreme wave heights due to meteotsunamis will increase.…”
Section: Will Climate Change Affect Future Tsunami Impacts?mentioning
confidence: 99%
“…Because meteotsunamis are shallow water waves over the shelf and coastal regions (wavelength C20 times the local depth), their amplitude can be affected by reflection, refraction, shoaling, diffraction and harbor resonance. Pattiaratchi and Wijeratne (2015) reviewed the occurrence of meteotsunamis worldwide with the aim of determining whether these ocean waves are an underrated hazard. They concluded that the probability of meteotsunamis worldwide is higher in general because energetic atmospheric disturbances are more probable than tsunamigenic earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Next, Meteorological and Hydrological Service will benefit from investigation a process which require non-standard meteo measurements, thus Features, processes, evolution and problems setting new standards for its operational forecast. The Mediterranean, European and world community in operational oceanography will benefit, as meteotsunamis are perceived as an underrated hazard that occur throughout the oceans (PATTIARATCHI & WIJERATNE, 2015). Various national ministries and civil protection agencies should be interested for project products, as being which are potential governmental users and possible organisers/sponsors for the establishment and maintenance of an operational oceanography centre.…”
Section: Potential Usersmentioning
confidence: 99%
“…Travelling air pressure disturbances are the most common generator of meteotsunamis, where the energy is transferred from the atmosphere to the ocean through a number of resonances, of which most common are Proudman resonance (PROUDMAN, 1929) and harbour resonance (RABINOVICH, 2009). At the top of a harbour these sea level oscillations can range for several metres and can flood coastal areas (VUČETIĆ et al, 2009), damage coastal infrastructure (JANSÀ et al, 2007;PATTIARATCHI & WIJERATNE, 2015), and injure and kill the people (HIBIYA & KAJIURA, 1982;BECHLE et al, 2016). Meteotsunamis has been documented to occur worldwide, while being particularly destructive in micro-tidal regions, where the coasts and the infrastructures are not adapted to large and rapid sea level oscillations.…”
Section: Introductionmentioning
confidence: 99%